Challenges in the Numerical Analysis of Centrifugal Pumps: Energetic, Cavitation and Dynamic Characteristics - Lipej, A. (Engineering, Technology & Applied Science Research, 2022)
Pumps are energetic devices that are present in a wide range of industries. Their installed power varies from a few tens of watts up to hundreds of megawatts. As the energy consumption is connected with global warming and climate change, the development of pumps that have good characteristics is very important. Theoretical and experimental methods have long been utilized in the development of pumps, but recently much research has been carried out with the help of Computational Fluid Dynamics (CFD) analysis. Certain numerical analyses can be of high quality and accurate, but special operational phenomena still occur, where special attention is required when performing analysis. This category includes operating regimes outside the Best Efficiency Point (BEP), the formation of inlet recirculation, cavitation, and the influence of wall roughness on all the above characteristics. The current paper presents the main problems that developers face when numerically analyzing the above-mentioned special operating regimes. Both numerical and experimental results are considered.